“Iba-Iba Tayo / We are All Different” - A Series of Public Service Announcements Awareness Video on Gender Identity - Sanding , Mervin Gallardo (International Journal of Sustainability and Advanced Integrated Research, 2026)
Gender diversity has reached an unprecedented peak, spanning from Baby Boomers to Generation Alpha. This evolution is central to UN Sustainable Development Goal 5 (SDG 5), which mandates dismantling restrictive norms to achieve global equality. While the WHO (2024) defines gender as socially constructed roles, recent Gallup (2025) data highlights a significant shift, with over 22% of Gen Z identifying as LGBTQ+. Despite this progress, gender stereotyping remains a persistent barrier. These "invisible boxes" pressure individuals to conform to rigid standards, causing systemic difficulties in career advancement—particularly the "glass ceiling"—and self-identity doubt (UNESCO, 2024). Furthermore, UN Women (2025) warns of a global "backlash" against gender rights in nearly 25% of countries. To address these challenges, researchers utilized a mixed-methods approach, interviewing 30 participants and surveying 200 individuals across four generations (Boomers, Gen X, Millennials, and Gen Z). These insights informed the creation of Public Service Announcement (PSA) videos designed to dismantle misconceptions regarding gender fluidity and expressionism (UNDP, 2025). By integrating personal narratives into these targeted messages, the study successfully raised awareness and promoted a more inclusive understanding of the gender spectrum, directly supporting the global mandate for equitable social transformation.